2019
DOI: 10.1016/j.jvs.2018.07.063
|View full text |Cite
|
Sign up to set email alerts
|

The use of video motion analysis to determine the impact of anatomic complexity on endovascular performance in carotid artery stenting

Abstract: Objective: Video motion analysis (VMA) uses fluoroscopic sequences to derive information on catheter and guidewire movement and is able to calculate two-dimensional catheter tip path length (PL) on the basis of frame-by-frame pixel coordinates. The objective of this study was to evaluate the effect of anatomic complexity on the efficiency of completion of defined stages of simulated carotid artery stenting as measured by VMA.Methods: Twenty interventionists each performed a standardized easy, medium, and diffi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 17 publications
(21 reference statements)
0
4
0
Order By: Relevance
“…ANGIO Mentor, a high-fidelity VR simulator, was validated by twelve studies as seen in Supplementary Table III . 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 Willaert et al. scored 2/2 for content by implementing an expert validated assessment scale on 20 endovascular experts and outlined a clear method of test design and standardization, scoring highly for response process (rating = 2/2).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…ANGIO Mentor, a high-fidelity VR simulator, was validated by twelve studies as seen in Supplementary Table III . 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 Willaert et al. scored 2/2 for content by implementing an expert validated assessment scale on 20 endovascular experts and outlined a clear method of test design and standardization, scoring highly for response process (rating = 2/2).…”
Section: Resultsmentioning
confidence: 99%
“…ANGIO Mentor, a high-fidelity VR simulator, was validated by twelve studies as seen in Supplementary Table III. [36][37][38][39][40][41][42][43][44][45][46][47] Willaert et al scored 2/2 for content by implementing an expert validated assessment scale on 20 endovascular experts and outlined a clear method of test design and standardization, scoring highly for response process (rating ¼ 2/2). 40 Maertens et al demonstrated in two studies that ANGIO Mentor could differentiate between endovascular performance in 32 surgical trainees and additionally 20 vascular surgeons and 29 medical students.…”
Section: Angioplasty and Stentingmentioning
confidence: 99%
“…In this study, the simulator served as a platform wherein the same cases could be repeated in a standardized environment; therefore, we were able to evaluate solely the navigational performance of the participant and the treatment modality. Rolls et al 27,28 used a similar method to evaluate catheter path length in CAS with varying anatomical complexity. The simulator metrics provide an objective and quantitative evaluation of the operator’s performance immediately after concluding the case.…”
Section: Discussionmentioning
confidence: 99%
“…[14][15][16] Researchers are also using VMA to study catheter movement on fluoroscopic images for potential applications. 17 Besides VMA, creative video compression algorithms can also be used to select out relevant highlight clips for efficient research analysis or audits. 18 Video processing algorithms will further maximize the research value of SAS video records.…”
Section: Researchmentioning
confidence: 99%